Improving Student Learning Outcomes Writing Simple Functional Sentences In The Two Stay Two Stray Technical Writing Learning Class VII SMPN 3 Kendari Academic Year 2022/2023 - La Nie (International Journal of Management and Education in Human Development, 2023)
The purpose of this Classroom Action Research is to: 1) Improving students' ability to write simple functional sentences in the past tense which is the basis for achieving the ability to create written texts in the form of recount. 2) Improving the teacher's ability to design and/or choose interesting learning models and techniques through an appropriate approach using pariah media so as to help create active, creative, effective, natural, meaningful and enjoyable learning. 3) Increase student motivation, especially in learning to write. The research was conducted in class VII SMPN 3 Kendari in the 2nd semester of the 2022/2023 school year with a total of 40 students, consisting of 14 male students and 26 female students. Based on the results of observations made by the teacher since the beginning of the second semester of the 2022/2023 school year in class VII, before PTK the value of student activity during the Writing learning process (BKOF-Written Cycle Stage) was 60.0% (enough). This is evidenced by the lack of enthusiasm of students in learning because writing teaching materials tend to be stiff and very bound to language rules/rules. Besides that, the learning models and techniques applied by the teacher seem to have been memorized by students so that students feel less challenged. After carrying out CAR, the results of observations in cycle I and cycle II showed very significant changes in student activity, which increased to very good (88.0%) in cycle I and (100%) in cycle II. The increase in student activity was accompanied by an increase in the average learning outcomes which jumped from the moderate category to the very high category, namely in cycle I it increased from (65.4%) to (80.5%) and in cycle II it rose again to (94, 2%). What is even more encouraging is that the average value of learning outcomes is accompanied by a very sharp increase in the percentage of the learning completeness level of students who score 8.0, that is, from (12.5%) students who have completed before PTK to (53 .8%) students have achieved mastery learning in cycle I and increased again to (92.5%) in cycle II.